Strategi Transliterasi pada Serat Ngelmu Bumi Asia untuk Mengoptimalkan Kemahiran Membaca Aksara Jawa - Wening Pawestri; Elis Suryani Nani Sumarlina; Ahmad Undang Darsa; Bani Sudardi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Javanese language lessons have been implemented in schools since elementary school. The decline in the interest and ability of the younger generation in reading Javanese script is a major challenge in preserving the cultural heritage of Indonesian literacy. This study aims to examine the transliteration strategy of the Serat Ngelmu Bumi Asia text as a pedagogical effort to optimize Javanese script reading skills in educational environments. Therefore, a study was conducted on grade X students of SMK Kita Bojonegoro to optimize Javanese script reading skills. The study was conducted using sources from ancient manuscripts and utilizing learning media to achieve optimal results. The method used in this study was a classroom action trial divided into two stages consisting of planning, action, observation/interpretation, and reflection. The results showed a significant increase in student abilities after the implementation of the transliteration strategy using learning media, with an average score increasing from the pre-cycle to the second cycle. Students who initially had difficulty reading Javanese script showed good progress, achieving higher mastery.